A pragmatic approach to service interaction filtering between call control services - Kolberg, Mario; Magill, Evan H. (Computer networks (Amsterdam, Netherlands : 1999), 2002)
Triggered by the deregulation of the telecommunications market, it is expected that the number of services deployed in the telecommunications network will increase dramatically in the near future. It is expected that these services will be interworking. However, as widely reported, interworking services will be subject to the service interaction problem. It is essential to cope with the problem in a developing multi service provider environment as it may substantially delay service deployment and hence form a serious obstacle to rapid service provisioning. In order to cope with the increasing number of services deployed in the network, previous work suggested the application of filtering approaches. This paper suggests such a technique. It is pragmatic in nature and does not require detailed service knowledge. Furthermore, it is shown how the approach can be incorporated into an overall comprehensive service interaction management process. Even though the approach is applied to call control aspects only, it could be extended to cover other areas.